2005
DOI: 10.2337/diabetes.54.6.1763
|View full text |Cite
|
Sign up to set email alerts
|

A Single Course of Anti-CD3 Monoclonal Antibody hOKT3γ1(Ala-Ala) Results in Improvement in C-Peptide Responses and Clinical Parameters for at Least 2 Years after Onset of Type 1 Diabetes

Abstract: Despite advances in understanding autoimmune diabetes in animal models, there has been little progress in altering the natural course of the human disease, which involves progression to insulin deficiency. Studies with immunosuppressive agents have shown short-term effectiveness, but they have not induced tolerance, and continuous treatment is needed. We studied the effects of hOKT3γ1(Ala-Ala), a humanized Fc mutated anti-CD3 monoclonal antibody, on the progression of type 1 diabetes in patients with recent-on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
514
2
9

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 602 publications
(541 citation statements)
references
References 25 publications
16
514
2
9
Order By: Relevance
“…An influence of age was not detected in the trial conducted by Herold et al This might be related to the different age range (7.5-30 years) or distribution in their study, or to its shorter follow-up [4,6]. The present finding that the effects of ChAglyCD3 are much more pronounced in younger patients can be explained by an age-dependency of the insulitis process.…”
Section: Discussioncontrasting
confidence: 59%
See 3 more Smart Citations
“…An influence of age was not detected in the trial conducted by Herold et al This might be related to the different age range (7.5-30 years) or distribution in their study, or to its shorter follow-up [4,6]. The present finding that the effects of ChAglyCD3 are much more pronounced in younger patients can be explained by an age-dependency of the insulitis process.…”
Section: Discussioncontrasting
confidence: 59%
“…The antibody-induced lowering of HbA 1c levels was also statistically significant when mean values were compared with those after placebo. In the study by Herold et al an antibody-effect on HbA 1c levels was reported for the first 18 months [6]. A reduction in glucose fluctuations and a lowering of HbA 1c levels are clinically relevant variables as they predispose to decreased risks for hypoglycaemic events [28] and chronic diabetes lesions, respectively [29].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ó 2007 Blackwell Publishing Ltd, Immunology, 121, [15][16][17][18][19][20][21][22][23][24][25][26][27][28] that over-expressed Foxp3 had increased numbers of Tregs in the periphery. [8][9][10] Dysregulation of Treg function has been implicated as an important event in the development of autoimmunity in animal models and in spontaneous autoimmune diseases in humans.…”
Section: Resultsmentioning
confidence: 99%